IMPORTANCE OF NANOTECHNOLOGY IN PHARMACEUTICAL FORMULATIONS -A REVIEW - A.K.M.P, Raihana; K, Ranjitha; P, Rishad; P.P, Sabeela; G R, Dr.Prasobh; Shrikumar, Dr.Sapna (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Nanotechnology has brought a revolution in manufacturing materials, creating a vast number ofnew devices, drug delivery systems and monitoring and diagnosing systems, but the implicationsif this technology are very diverse, impacting consumers, clinicians and the practice ofinformatics. A major area of concern for health care providers is the ethical use of nanomaterials.Nanotechnology is manipulation of matter on an atomic, molecular, and supramolecular scale.The earliest, widespread description of nanotechnology referred to the particular technologicalgoal of precisely manipulating atoms and molecules for fabrication of macroscale products, alsonow referred to as molecular nanotechnology. Drugs with high toxic potential like cancerchemotherapeutic drugs can be given with a better safety profile with the utility ofnanotechnology. These can be made to act specifically at the target tissue by active as well aspassive means. Other modalities of therapy such as heat induced ablation of cancer cells bynanoshells and gene therapy are also being developed. This review discusses the variousplatforms of nanotechnology being used in different aspects of medicine like diagnostics andtherapeutics. The potential toxicities of the nanoparticles are also described in addition tohypothetical designs such as respirocytes and microbivores. The safety of nanomedicine is notyet fully defined. However, it is possible that nanomedicine in future would play a crucial role inthe treatment of human diseases and also in enhancement of normal human physiology.